Distance Education in Ghana: Assessing Students Readiness for Information Communication Integration - Qua-Enoo, Albert; Bervell, Brandford; Nyagorme, Paul; Edumadze, John K. E. (West African Journal of Open and Flexible Learning, 2023)
Distance education is increasingly becoming a major alternative to traditional education with higher institutions vying for global students over the past decade. This article assesses students’ readiness for information and communication technology in distance learning in Ghana. Students from higher institutions were surveyed using the cluster sampling method. The SPSS version 21 software was used to analyse the data and generate both descriptive and inferential statistics such as cross-tabulation, chi-square and one-way ANOVA. The findings of the study included low computer literacy of computer-based online learning systems, high expenditure on internet data, and low but effective online study community using social media. Online resource usage categories were found to differ between students for different institutions. Also, confidence in using computer to learn does not correlate with internet usage history. The study concluded that solid foundation in computer literacy at the preceding educational level is critical to easy adoption and integration of ICT at the tertiary level. Finally, we recommend the promotion of more online learning communities for learners and with their lecturers. Résumé : L’enseignement à distance devient de plus en plus une alternative majeure à l’enseignement traditionnel, les établissements d’enseignement supérieur se disputant les étudiants du monde entier au cours de la dernière décennie. Cet article évalue l’état de préparation des étudiants aux technologies de l’information et de la communication dans le cadre de l’enseignement à distance au Ghana. Les étudiants des établissements d’enseignement supérieur ont été interrogés à l’aide de la méthode d’échantillonnage en groupes. Le logiciel SPSS version 21 a été utilisé pour analyser les données et générer des statistiques descriptives et inférentielles telles que les tableaux croisés, le chi-carré et l’ANOVA à sens unique. Les résultats de l’étude comprennent une faible connaissance informatique des systèmes d’apprentissage en ligne basés sur l’ordinateur, des dépenses élevées en données Internet, et une communauté d’étude en ligne peu nombreuse mais efficace utilisant les médias sociaux. Les catégories d’utilisation des ressources en ligne diffèrent d’un étudiant à l’autre en fonction de l’établissement. En outre, la confiance dans l’utilisation de l’ordinateur pour apprendre n’est pas en corrélation avec l’historique de l’utilisation de l’internet. L’étude conclut qu’une base solide de connaissances informatiques au niveau éducatif précédent est essentielle pour faciliter l’adoption et l’intégration des TIC au niveau tertiaire. Enfin, nous recommandons de promouvoir davantage de communautés d’apprentissage en ligne pour les apprenants et leurs professeurs